Identification of the potato (Solanum tuberosum L.) P-type ATPase gene family and investigating the role of PHA2 in response to Pep13 - Zhang, Feng; Yuan, Anping; Nie, Zongyue; Chu, Moli; An, Yanlin (Frontiers in Plant Science, 2024)
P-type ATPase family members play important roles in plant growth and development and are involved in plant resistance to various biotic and abiotic factors. Extensive studies have been conducted on the P-type ATPase gene families in Arabidopsis thaliana and rice but our understanding in potato remains relatively limited. Therefore, this study aimed to screen and analyze 48 P-type ATPase genes from the potato (Solanum tuberosum L.) genome database at the genome-wide level. Potato P-type ATPase genes were categorized into five subgroups based on the phylogenetic classification of the reported species.Additionally, several bioinformatic analyses, including gene structure analysis, chromosomal position analysis, and identification of conserved motifs and promoter cis-acting elements, were performed. Interestingly, the plasma membrane H + -ATPase (PM H + -ATPase) genes of one of the P3 subgroups showed differential expression in different tissues of potato. Specifically, PHA2, PHA3, and PHA7 were highly expressed in the roots, whereas PHA8 was expressed in potatoes only under stress. Furthermore, the small peptide Pep13 inhibited the expression of PHA1, PHA2, PHA3, and PHA7 in potato roots.Transgenic plants heterologously overexpressing PHA2 displayed a growth phenotype sensitive to Pep13 compared with wild-type plants. Further analysis revealed that reducing potato PM H + -ATPase enzyme activity enhanced resistance to Pep13, indicating the involvement of PM H + -ATPase in the physiological process of potato late blight and the enhancement of plant disease resistance. This study confirms the critical role of potato PHA2 in resistance to Pep13.